Development of hollow fiber membranes for solvent resistant nanofiltration - Lim, Siow Kee (2017)
Solvent-resistant nanofiltration (SRNF) is an emerging membrane-based separation technology that can separate molecules of 200-1000 Da in various organic solvents efficiently. It has the potential to replace or be combined with traditional separation processes in industry to lower energy consumption and reduce waste. As hollow fiber membranes can offer advantages over flat sheet membranes and are not known to be commercially available for SRNF applications, this study aims to develop hollow fiber membranes that can perform nanofiltration in challenging polar aprotic solvents such as dimethylformamide (DMF) at a lower operating pressure than existing SRNF membranes.